(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
As is known, the task of industrial training practice is to train qualified personnel for modern manufacturing enterprises, to consolidate and improve the knowledge and skills of future metrologist engineers in the professions they are studying [1;2]. Later, a working program was developed for the training direction "Metrology, Standardization and Quality Management" of higher technical educational institutions: 60711300-"Introduction (Production) Practice in the Profession of Metrology, Standardization and Quality Management".